Identification of Alkaloids of Pepper (Piper Nigrum) and Kadok (Piper Sarmentosum) and the Biotransformation of Piperine Using Aspergillus Niger - Lim, Chyi Meei (2008)
Studies have been carried on the roots of Piper nigrum and the aerial parts of Piper sarmentosum. Their alkaloidal components and biological properties are reported in this thesis. The major compound of the Piper nigrum, piperine (85) was biotransformed by Aspergillus niger FTCC 5003 yielded one piperine derivative, a new natural product 5-[3,4-(methylenedioxy)phenyl]-pent-2-ene piperidine (88). These alkaloidal components were isolated using common chromatographic techniques and were identified using spectroscopic experiments such as NMR, MS, IR and UV. The roots of Piper nigrum furnished eight alkaloids, Cepharadione A (81), Piperolactam (82), 2,4-tetradecadionoic acid isobutyl amide (83), (E)-1-[3’,4’-(Methylenedioxy)cinnamoyl]piperidine (84), Piperine (85), Pellitorine (1), Sylvamide (86) and Paprazine (87). The compounds 2,4-tetradecadionoic acid isobutyl amide (83) and (E)-1-[3’,4’-(Methylenedioxy)cinnamoyl]piperidine (84) were first obtained as natural products and new to this species of plants. Beside that, Paprazine (87) never had been isolated from this species of plant. Meanwhile from the biotransformation of Aspergillus niger FTCC 5003 yielded one new compound, (88). Up to now, biotransformation research has only been carried out on the terpenoid compounds and a few on alkaloids. Meanwhile, investigations on the aerial parts of Piper sarmentosum gave one alkaloidal compound, 1-nitrosoimino-2,4,5-trimethoxybenzene (89). This compound was first isolated from this plant and also a new found natural product The petroleum ether and chloroform extracts of Piper nigrum roots were active against HL-60 cell line with the IC50 values of 9.8 and 11.2 μg/ml, respectively. However the ethyl acetate extract of Piper nigrum was inactive to HL-60 cell line. Meanwhile, the hexane and ethyl acetate extracts of Piper sarmentosum showed good cytotoxic activity with the IC50 values of 14.4 and 9.8 μg/ml respectively on MCF-7 cell line. Meanwhile the methanol extract of the aerial parts of Piper saramentosum was inactive on MCF-7 cell line. Cytotoxic test on HeLa cell line also been carried out on the various extracts of Piper sarmentosum. However, only hexane extract gave active result with the IC50 value of 11.6 μg/ml. Two pure compounds from Piper nigrum (E)-1-[3’,4’-(Methylenedioxy)cinnamoyl]piperidine (84) and Pellitorine (1) were tested on HeLa and MCF-7 cell lines. Pelltorine (1) showed good activities against MCF-7 and HeLa cell line with the IC50 value of 1.8 and 13 μg/ml, respectively. The extracts of Piper sarmentosum and pure compounds of Piper nigrum were never tested on HeLa and MCF-7 cell lines. This is the first report on them. The antimicrobial assay was carried out towards four pathogenic bacteria, Methicillin Resistant Staphylococcus aures, Pseudomonas aeruginose, Staphylococcus typhimurium and Bacillus subtilis. The antifungal activity testing of the plant extracts were carried out against the fungi Candida albican, Apergillus ochraceaus, Sacchoromycs cerevisiae and Candida lypolytica. No activity was observed for all the extracts on these two assays. The larvicidal tests performed against the larvae of Aedes aegypti. The acid base treated ethanol extract of Piper nigrum showed a strong activity against the larvae with the LC50 value of 1.88 μg/ml. The pure compound, pellitorine (1) also gave good activity as the LC50 value is 6.22 μg/ml. The hexane and ethyl acetate extracts of Piper sarmentosum gave strong activities with the LC50 values of 8.08 and 6.94 μg/ml, respectively. Meanwhile the methanol extract of Piper sarmantosum was not active towards the larvae of Aedes aegypti. The acid base treated ethanol extract of Piper nigrum was first performed against the larvae of Aedes aegypti in this study.